Kesiapan Sekolah dalam Melaksanakan Pendidikan Inklusif di Sekolah Dasar Inklusi Kabupaten Pacitan Wilayah Timur - Aminulloh, Alfan Saifut; Purnamasari, Mega Isvandiana; Erviana, Lina (PGSD STKIP PGRI Pacitan, 2024)
This study aims to 1) know the physical readiness and infrastructure in the process of implementing inclusion education, 2) know the readiness of human resources in the process of implementing inclusion education, 3) know the obstacles in organization of inclusion education. The data collection techniques this study were observation, interviews, and documentation. The results showed that 1) the percentange of readiness of facilities and infrastructure reached 62,5%, identifying that both schools are ready to carry out inclusion education, 2) human resource readiness is also fulfilled with more than 2 trained Companion Teachers at both schools, 3) the obstacles faced in implementing inclusive education include several support facilities such as learning media and the absence of aksebilitas for children with special needs and lack of attention from students parents.